Pengaruh Return on Asset dan Return on Equity terhadap Harga Saham Pada Pt. Fajar Surya Wisesa Tbk Periode 2020-2024 - Rumaisha Rahayu; Tiara Diva Maharani Keliat; Aulia Rahma; Annisa Annisa; Keisya Desputri (Rashid : Journal of Economic, 2026)
Stock prices can be influenced by various financial performance factors, including Return on Assets (ROA) and Return on Equity (ROE). This study aims to examine the effect of Return on Assets (ROA) and Return on Equity (ROE) on stock prices both partially and simultaneously. The unit of analysis in this study is PT Fajar Surya Wisesa Tbk during the period 2020–2024. This research employs a quantitative descriptive approach. The population of this study consists of the company’s financial statements, with purposive sampling used as the sampling technique, resulting in a total of five annual observations. Data analysis was conducted using classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test and F-test) with the assistance of SPSS software. The results indicate that, partially, Return on Assets (ROA) has a negative and insignificant effect on stock prices, while Return on Equity (ROE) has a positive but insignificant effect on stock prices. Simultaneously, Return on Assets (ROA) and Return on Equity (ROE) do not have a significant effect on the stock prices of PT Fajar Surya Wisesa Tbk.